Postoperative nausea and vomiting in orthognathic surgery: systematic review and meta-analysis - Grillo, Ricardo; Borba, Alexandre Meireles; Brozoski, Mariana Aparecida; da Silva, Yuri Slusarenko; Samieirad, Sahand; Naclério-Homem, Maria da Graça (Oral and maxillofacial surgery, 2024)
Purpose Postoperative nausea and vomiting (PONV) is a frequently reported adverse event following orthognathic surgery. The aim of this work is to conduct a systematic review of the literature on the subject, and to discuss the role of maxillofacial surgeons and the steps that can be taken to prevent or control PONV in orthognathic surgery. Methods A systematic review was conducted according to the PRISMA guidelines, using the search strategy: (orthognathic AND (nausea OR vomiting)). The authors searched PubMed, Embase, Dimensions, Web of Science and Google Scholar databases, without any language restrictions. RevMan 5.4 was used to create a risk of bias graph and a forest plot. Results The included articles were classified as having a low risk of bias, despite the limited literature on the subject. Various measures have been reported to be beneficial in preventing or managing PONV, such as the use of dexamethasone, antiemetic drugs, gastric aspiration, and anesthetic blocks. Effective bleeding control and faster surgeries can also be helpful. Conclusions Throat packs have not been found to be effective in preventing PONV. Although no definitive protocol has been established in the literature, the Enhanced Recovery After Surgery (ERAS) protocol could be a useful approach. Overall, a multimodal approach may be taken to prevent PONV, and further research is needed to establish definitive protocols.